Analisis Strategi Pemasaran dan Penetapan Harga Dalam Meningkatkan Volume Penjualan pada CV. Kartika Ayu - Radhika Narwastu; Hendra Saputra; Irma Bonita Simbolon; Cecilia Miranda Lumbangaol; Peby Monica (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effectiveness of the marketing strategies and pricing adopted by CV Kartika Ayu, a company engaged in the sale of ornamental plants, in increasing sales volume. The research employs a qualitative approach, using data collection techniques such as in-depth interviews, observations, and document analysis. The results indicate that marketing strategies, including the use of social media, exhibitions, and partnerships with home decor stores, significantly contribute to raising consumer awareness and interest. Competitive and flexible pricing also proves effective in attracting various market segments. The study concludes that the right combination of marketing strategies and strategic pricing can significantly increase the sales volume of CV Kartika Ayu. The study recommends continuously optimizing digital marketing strategies and periodically evaluating pricing policies to adapt to market dynamics and consumer preferences.